Simulation results of a shunt active power filter with control based on p-q theory - Couto, Emílio F. (2003)
The present paper describes a shunt active power filter with a control system based on the p-q theory, and studies its performance through simulation results obtained with different types of loads. It is explained, in a brief form, the p-q theory and its application in the control of a shunt active power filter. Matlab/Simulink was the simulation tool, used in the study, development, and performance evaluation of the shunt active power filter controller. The simulations were carried out for different loads, of linear and non-linear types. The shunt active power filter allows compensating harmonic currents, reactive power, unbalanced loads, and zero-sequence currents, presenting a good dynamic and steady-state performance, as it can be observed in the simulation results.